THE GUIDANCE AND COUNSELING ON THE COVID-19 PANDEMIC PERIOD - Dwi Rohmadi; Achadi Budi Santosa; Apri Winge Adindo (UIR Press, 2021)
The Covid19 pandemic that came suddenly has demanded a radical change in the learning system. Many are not ready for the change in the system, schools are constrained in providing services to their students, as well as the way teachers provide learning to their students. This problem is also faced by guidance and counseling teachers in providing services to their students. The purpose of this study was to uncover guidance and counseling teacher services, student responses, and barriers to guidance and counseling services during the Covid19 pandemic. The method used is a qualitative approach to the phenomenological model. The results showed that the guidance and counseling services provided by teachers during the Covid19 pandemic were not optimal. Student responses in receiving services vary. Each subject experienced different obstacles, most students were constrained in taking virtual lessons, did not have cellphones, did not have laptops, the ability to buy credit was very limited, and internet network access was unstable so that students became constrained in learning.